Multi‐institutional experience of genetic diagnosis in Ecuador: National registry of chromosome alterations and polymorphisms. Issue 2 (12th December 2019) - Paz‐y‐Miño, César; Yumiceba, Verónica; Moreta, Germania; Paredes, Rosario; Ruiz, Mónica; Ocampo, Ligia; Llamos Paneque, Arianne; Ochoa Pérez, Catalina; Ruiz‐Cabezas, Juan Carlos; Álvarez Vidal, Jenny; Jiménez Torres, Idarmis; Vargas‐Vera, Ramón; et al.
Abstract: Background: Detection of chromosomal abnormalities is crucial in various medical areas; to diagnose birth defects, genetic disorders, and infertility, among other complex phenotypes, in individuals across a wide range of ages. Hence, the present study wants to contribute to the knowledge of type and frequency of chromosomal alterations and polymorphisms in Ecuador. Methods: Cytogenetic registers from different Ecuadorian provinces have been merged and analyzed to construct an open‐access national registry of chromosome alterations and polymorphisms. Results: Of 28, 806 karyotypes analyzed, 6, 008 (20.9%) exhibited alterations. Down syndrome was the most frequent autosome alteration (88.28%), followed by Turner syndrome (60.50%), a gonosome aneuploidy. A recurrent high percentage of Down syndrome mosaicism (7.45%) reported here, as well as by previous Ecuadorian preliminary registries, could be associated with geographic location and admixed ancestral composition. Translocations (2.46%) and polymorphisms (7.84%) were not as numerous as autosomopathies (64.33%) and gonosomopathies (25.37%). Complementary to conventional cytogenetics tests, molecular tools have allowed identification of submicroscopic alterations regions or candidate genes which can be possibly implicated in patients' symptoms and phenotypes. Conclusion: The Ecuadorian National Registry of Chromosome Alterations and Polymorphisms provides a baseline to better understand chromosomal abnormalities in Ecuador and therefore their clinical management and awareness. This data will guide public policy makers to promote and financially support cytogenetic and genetic testing. Abstract : Of 28, 806 karyotypes analyzed in Ecuador, 6, 008 (20.9%) exhibited alterations. Down syndrome was the most frequent autosome alteration (88.28%), followed by Turner syndrome (60.50%). Translocations (2.46%) and polymorphisms (7.84%) were not as numerous as autosomopathies (64.33%) and gonosomopathies (25.37%).